THE ACTIVE MUSIC THERAPY AS A FORM OF SOCIAL REHABILITATION FOR DRUG ADDICTS IN WAY HUWI DEPARTMENT OF CORRECTIONS IN LAMPUNG PROVINCE - Zainudin Hasan; Zainab Ompu Jainah; Erlina B (University of Sang Bumi Ruwa Jurai, 2018)
The music therapy is the use of music intervention together with its elements by professionals in a therapeutic relation to obtain a particular objective. Why the music therapy is chosen as a rehabilitation media for drug addicts? Of course, because music is a fun activity which is relatively safe and good and this is one of social rehabilitation concepts by helping to recognize and accept different emotion types, to develop expressive abilities and self-awareness, to improve self-confidence, and facilitate relaxation to reduce stress. Based on the research conducted by the authors by using music therapy model for social rehabilitation, the authors conclude that music therapy for recovery of drug addicts can be done in two ways; passive and active music therapies. During the research in Way Huwi Department of Corrections for drug abusers, in Lampung province, by using passive music therapy, the research objects only reached a stage of having calm feeling, but did not yet reach the change of mindset stage significantly to leave old habits and to change into new habits, while activities in active music therapy such as singing, writing songs, improvisation, and doing performances which have therapy elementstend to provide more maximum roles than just listening music.